The advantages of dairying to the Kansas farmer of limited capital - Blair, Albert Edwin (My University, 1899)
Introduction: Relation of Feeds to Quantity and Quality of Milk. In general, the largest quantity of milk is obtained when the conditions are the same as those in June; i.e., when there is plenty of appetizing, succulent food, rich in materials contained in milk. The various grasses, usually found in pastures, contain these ingredients in an appetizing form. Foods should contain protein, carbohydrates and fats. Protein includes those materials which contain nitrogen. Milk, blood, muscle, hair, brain and nerves contain protein in their makeup. Protein must be present as there is no substitute. In addition to the above, protein may furnish eat and energy to the body, and may also be transformed into fat. Fat includes all fatty substances found in feeds. It furnishes heat, energy, and fat for the animal. One pound of fat is worth 2.2 pounds of protein or carbohydrates for heat production. Carbohydrates include starches, sugars, gums, and similar substances. They also furnish heat, energy, and fat to the body. A good ration for an average 1000 pound cow should contain 2.5 pounds protein, 12.5 pounds carbohydrates and .4 of a pound of fat.
Citation: Blair, Albert Edwin. The advantages of dairying to the Kansas farmer of limited capital. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Relation of Feeds to the Quantity and Quality of Milk; Feed's Ingredients; Importance of Water; Salt; Theses; Manuscripts (documents)